Atletismo na educação física escolar: a elaboração colaborativa do software Atletic - Gemente, Flórence Rosana Faganello [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The changes caused by Digital Technologies of Information and Communication (DTIC) present new challenges for Education, which must incorporate these technologies, provide new mediations and pedagogical proposals to meet the changing needs of society. In today's context and the evidence of the lack of teaching materials targeted to athletics and the difficulty that physical education teachers still find to work with that content in their classes, the general objective of this research was to develop, collaboratively, a software with teachers of Physical Education for the process of teaching and learning in school athletics. The specific objective was to analyze the collaborative development process of a software, checking its challenges and contributions in the training of teachers and the work with athletics with the insertion of DTIC in school. The methodology used is qualitative, with action-research elements. The research was developed in two stages that are complementary, the first module of the course of continuing training of teachers, called Athletics Pedagogy, with the participation of 21 teachers of Physical Education from Municipal schools in Goiânia, was conducted using a survey of difficulties and needs of the teachers in the development of the work with athletics in Physical Education classes; studies were conducted, reflections, discussions and experiences directed to athletics, and the software ATLETIC was developed, which addresses the events of the high jump, pole vault, javelin throw, discus throw, hammer throw, and weight throw, according to suggestions, needs, and interests presented by the teachers. The second stage of the research was completion of the second module of the course Athletics Pedagogy, with the participation of 13 teachers who participated in the first stage of the research. At this stage, we deepen the discussion on the entry of DTIC in physical education classes, especially considering the...

As transformações ocasionadas pelas Tecnologias Digitais de Informação e Comunicação (TDICs), apresentam novos desafios para a Educação, que precisa incorporar essas tecnologias, proporcionar novas mediações e propostas pedagógicas para atender as novas necessidades da sociedade. Diante do atual contexto e da constatação da falta de materiais didáticos direcionados ao atletismo e da dificuldade que os professores de Educação Física Escolar ainda encontram para trabalhar com esse conteúdo em suas aulas, o objetivo geral desta pesquisa foi desenvolver, colaborativamente, um software com professores de Educação Física para o processo de ensino e aprendizagem do atletismo na escola. Por sua vez, o objetivo específico foi analisar o processo de desenvolvimento colaborativo de um software, verificando seus desafios e contribuições para a formação dos professores e para o trabalho com o atletismo com a inserção das TDICs na escola. A metodologia utilizada é de natureza qualitativa, com elementos da pesquisa-ação. A pesquisa foi desenvolvida em duas etapas que se complementam, sendo a primeira a realização do primeiro módulo do curso de formação continuada de professores, denominado Pedagogia do Atletismo. Com a participação de 21 professores de Educação Física de escolas da Rede Municipal de Goiânia, realizamos o levantamento das dificuldades e necessidades dos professores no desenvolvimento do trabalho com o atletismo nas aulas de Educação Física; realizamos estudos, reflexões, discussões e vivências direcionadas ao atletismo e desenvolvemos o software ATLETIC, o qual aborda as provas do salto em altura, salto com vara, lançamento do dardo, lançamento do disco, lançamento do martelo e arremesso do peso, a partir das sugestões, necessidades e interesses apresentados pelos professores. A segunda etapa da pesquisa ocorreu com a realização do segundo módulo do curso Pedagogia do Atletismo...
Keywords: Athletics; Atletismo; Atletismo - Estudo e ensino; Software; Tecnologias de informação e comunicação; Software - Desenvolvimento; Professores - Formação